Faktor-Faktor Yang Mempengaruhi Kepuasan Pelanggan Terhadap Pengurusan Organisasi Di Kampung Budaya Mari-Mari, Sabah - Gadung Aflin, Tagko. (Universiti Malaysia Sarawak (UNIMAS), 2018)
This study was conducted to study the Factors that Influence Customer Satisfaction towards organizational management at Mari-Mari Cultural Village, Sabah. The objective of this study is to analyze the relationship between price, employee attitude, and the facilities provided with customer satisfaction. This study was conducted using quantitative methods, by circulating a questionnaire to 250 respondents and conducting data analysis using Statistical Packages for the Social Science (SPSS). Based on the analysis conducted, researcher found that the price, the attitude of the employees, and the facilities provided were factors that influenced the customer satisfaction that came to Mari-Mari Cultural Village.